2022
DOI: 10.1039/d2dt01698b
|View full text |Cite
|
Sign up to set email alerts
|

LiSrSbS3: parallel configurations of lone pair electrons inducing a large birefringence

Abstract: By optimizing the arrangement of [SbS3] trigonal pyramid with stereochemically active lone pair electrons, a new compound with large birefringence was designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…37 Raman peaks below 200 cm −1 are mainly responding to the vibration of Na–S or K–S bonds. Between 200–400 cm −1 , some peaks can be assumed to be the M n + –S bond vibrations, such as 220 and 283 cm −1 for Mg–S (Na 4 MgP 2 S 8 ); 241, 284 and 300 cm −1 for Cu–S (K 3 CuP 2 S 6 ); 299 cm −1 for Zn–S (Na 2 ZnP 2 S 6 ); 376 cm −1 for Ga–S (KGaP 2 S 6 ); and 320 and 336 cm −1 for Sb–S (Na 3 SbP 2 S 6 ), which are also consistent with other known sulfides, such as the Mg–S bond vibrations in Li 4 MgGe 2 S 7 (216 cm −1 ) 38 and SrMgGeS 4 (266.56 cm −1 ); 39 Cu–S bond vibrations in Cu 3 PS 4 (239, 282, 299 cm −1 ); 37 Zn–S and Ga–S bond vibrations in Na 6 Zn 3 Ga 2 S 9 (303, 378 cm −1 for Zn/Ga–S) and Na 6 Zn 3 In 2 S 9 (301, 347 cm −1 for Zn/In–S); 40 and Sb–S bond vibrations in LiSrSbS 3 (333 cm −1 ) 41 and (CuI) 2 Cu 3 SbS 3 (321 cm −1 ). 42…”
Section: Resultsmentioning
confidence: 99%
“…37 Raman peaks below 200 cm −1 are mainly responding to the vibration of Na–S or K–S bonds. Between 200–400 cm −1 , some peaks can be assumed to be the M n + –S bond vibrations, such as 220 and 283 cm −1 for Mg–S (Na 4 MgP 2 S 8 ); 241, 284 and 300 cm −1 for Cu–S (K 3 CuP 2 S 6 ); 299 cm −1 for Zn–S (Na 2 ZnP 2 S 6 ); 376 cm −1 for Ga–S (KGaP 2 S 6 ); and 320 and 336 cm −1 for Sb–S (Na 3 SbP 2 S 6 ), which are also consistent with other known sulfides, such as the Mg–S bond vibrations in Li 4 MgGe 2 S 7 (216 cm −1 ) 38 and SrMgGeS 4 (266.56 cm −1 ); 39 Cu–S bond vibrations in Cu 3 PS 4 (239, 282, 299 cm −1 ); 37 Zn–S and Ga–S bond vibrations in Na 6 Zn 3 Ga 2 S 9 (303, 378 cm −1 for Zn/Ga–S) and Na 6 Zn 3 In 2 S 9 (301, 347 cm −1 for Zn/In–S); 40 and Sb–S bond vibrations in LiSrSbS 3 (333 cm −1 ) 41 and (CuI) 2 Cu 3 SbS 3 (321 cm −1 ). 42…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, incorporating the cation centered with stereochemical‐active long pairs or the Jahn–Teller effect, π‐conjunction planar units, and mixed‐anion units [ 14 ] is usually applied to chalcogenides to generate highly distorted polyhedrons, corresponding to the favorable increase of crystal birefringence, such as PbGa 4 Se 7 , [ 15 ] La 2 CuSbS 5 , [ 16 ] and LiSrSbS 3 . [ 17 ] The improvement of birefringence in IR NLO materials has focused on theoretically calculated values, and experimental birefringence in chalcohalide remains scarcely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Optical components such as optical circulator, beam splitters, , electro-optics Q switch, optical isolators, , achromatic quarter waveplates ,, and phase compensators ,, are realized using birefringent crystals. Currently, noncentrosymmetric oxides have been extensively investigated as outstanding birefringent materials. ,, Oxide birefringent crystals such as TiO 2 , YVO 4 , LiNbO 3 , CaCO 3 , and α-BaB 2 O 4 , with birefringence ranging from 0.256 to 0.122 in the visible range are used commercially. , In spite of a few exceptions ,− birefringent materials have been almost exclusively limited to oxides to date. Recently, halide perovskites emerged as potential energy materials owing to the impressive optical and electronic properties. In comparison, the possibility of halide perovskites being birefringent materials has long been overlooked. Recently, birefringence was observed from the mixed halide or hybrid halide perovskite materials. ,,, Chen et al reported the fabrication of achromatic quarter-wave plates using inorganic Cs 4 PbBr 6 crystals embedded with perovskite CsPbBr 3 nanocrystals .…”
mentioning
confidence: 99%